Real drugs in a virtual world: drug discourse and community online - Murguía, Edward (Lexington Books, 2007)
Introduction -- Club drugs, online communities, and harm reduction websites on the Internet / Edward Murguía, Melissa Tackett-Gibson & Rachel Willard -- The body or the body politic? : risk, harm, moral panic and drug use discourse online / Sarah N. Gatson -- The new drugs Internet survey : a portrait of respondents / Edward Murguía & Melissa Tackett-Gibson -- Causal factors in drug use : a phenomenological approach based on Internet data / Edward Murguía -- Voluntary use, risk, and online drug-use discourse / Melissa Tackett-Gibson -- Deterrence of harm to self : a study of online rhetoric / Azzurra Crispina -- Assessing the likelihood of Internet information-seeking leading to offline drug use by youth / Sarah N. Gatson -- Scripters and freaks : knowledge and use of prescription stimulants online / Melissa Tackett-Gibson -- Illegal behavior and legal speech : Internet communities' discourse about drug use / Sarah N. Gatson -- Music as a feature of the on-line discussion of illegal drugs / Joseph A. Kotarba -- The neverending conversation : a case study of rave-related Internet conversation and drug use / Ann Lessem -- Using popular music to interpret the drug experience / Shawn Halbert & Joseph A. Kotarba -- A review of Internet studies in this volume, an examination of root causes of drug abuse from a societal point of view, and some possible solutions / Edward Murguía & Ann Lessem